Penggunaan Media Sosial Terhadap Pemasaran Produk UMKM: (Studi Deskriptif Kualitatif Pada Toko Aplikasi Premium “Cece”) - Esaskia Silalahi, Putri; Kiara Fitria, Putri; Nabilah, Rizky; Alfridho, Muhammad Adrian; Al Gozi Nasution, Ahmed; Harahap, Nursapia (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to determine the mechanisms, strategies, roles, benefits and obstacles of using social media for marketing Toko Cece. This type of research is qualitative research with primary data sources is research conducted at Cece's Premium Application Store and secondary data is supporting data obtained through literature review or reading sources such as books, articles and essays. The data analysis technique used in this research is using steps, data reduction, data presentation and conclusion drawing. The results of this study illustrate that social media has a role and benefits in Toko Cece. Social media plays a very important role in UMKM marketing. Toko Cece relies heavily on social media as a place to sell and a place to promote business products. And Toko Cece has also thought about social media strategies to expand the business market so that the scale of the business can grow again. For obstacles that occur in promoting products through social media, namely the frequent suspension of Toko Cece's social media accounts.